Advances in Multimedia Information Processing – PCM 2007
DOI: 10.1007/978-3-540-77255-2_35
|View full text |Cite
|
Sign up to set email alerts
|

A New Adaptation Method for Speaker-Model Creation in High-Level Speaker Verification

Abstract: Abstract. Research has shown that speaker verification based on highlevel speaker features requires long enrollment utterances to be reliable. However, in practical speaker verification, it is common to model speakers based a limited amount of enrollment data. To minimize the undesirable effect of insufficient enrollment data on system performance, this paper proposes a new adaptation method for creating speaker models based on high-level features. Different from conventional methods, the proposed adaptation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…And the MAP adaptation described in [10] is applied to create the adapted speaker models (2) where, β c ∈ [0, 1] is a phonetic class-dependent adaptation coefficient controlling the contribution of the speaker data and the background models (Eq. 1) on the MAP-adapted model.…”
Section: Af-based Supervectorsmentioning
confidence: 99%
“…And the MAP adaptation described in [10] is applied to create the adapted speaker models (2) where, β c ∈ [0, 1] is a phonetic class-dependent adaptation coefficient controlling the contribution of the speaker data and the background models (Eq. 1) on the MAP-adapted model.…”
Section: Af-based Supervectorsmentioning
confidence: 99%
“…However, the client models that they created are essentially a linear weighted sum of enrollment data's distribution and background models. It was found that the modeling capability of the AFCPMs drops rapidly when the amount of enrollment data decreases [36,37].…”
Section: Introductionmentioning
confidence: 99%